SOSIALISASI PKM DIGITAL SISTEM INFORMASI MANAJEMEN PENINGKATAN BELANJA ONLINE DI ERA PANDEMI COVID-19 - Lutfiah, Anisa; Indra; Hertati , Lesi; Terttiaavini; Heryati, Agustina; Asmawati (Transpublika Publisher, 2021)
In today's business world, advances in information technology have been effectively harnessed. E-commerce, facilitated through the internet, has emerged as a means to significantly reduce transaction costs. The internet has become an integral part of our daily lives, making E-commerce a widely adopted practice. It involves the use of communication networks and computers to carry out business processes, enabling internet users with web browsers to buy and sell products. It is important to note that while E-commerce falls under the umbrella of e-business, not all e-business activities are encompassed by E-commerce. E-business has a broader scope, encompassing the use of technology to drive business operations and generate significant impacts on the overall organization. The pandemic has brought about substantial changes, including shifts in work patterns, learning methods, and shopping habits. Government-imposed mobility restrictions and the high number of Covid-19 cases have led to concerns about venturing outside. However, the essential requirements of daily life cannot be disregarded.